Legal mobilization and climate change - Anna-Maria Marshall; Susan M Sterett (Oñati Socio-Legal Series)
Climate change is a wicked problem, a framework not often used in sociolegal studies. The problem is complex, not readily named, and not limited to one jurisdiction. Therefore, the places of law are multiple: human rights instruments, supranational tribunals, regional courts, and local governments and NGOS. Litigation concerning responsibility for greenhouse gas emissions has largely not resulted in favorable judgments, and the papers in this collection turn to other ways of conceptualizing law and courts in responding to climate change. Relevant legal strategies include environmental legal enforcement, but also changes in investment, and response to the many disasters that are related to climate change. The papers in this collection travel across jurisdictions, actors and problems to assess legal strategies concerning climate change.